Microbiological quality of keropok lekor during processing - Mahmud @ Ab. Rashid, Nor Khaizura; Hassan, Zaiton; Bakar, Jamilah; Rahmat Ali, Gulam Rusul (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Keropok lekor is an important fish product in Malaysia. The customer demands for keropok lekor have been increasing. This study was conducted to analyze the microbiological quality of keropok lekor in every stage of its processing, namely mincing, mixing, kneading, boiling and cooling. When processing keropok lekor, the boiling of keropok lekor at 100°C for 10 min reduced the Total Plate Counts (4.38±0.47 log10 cfu/g), psychrotrophic counts (2.00 ± 0.00 log10 cfu/g), mesophilic sporeformer counts (1.26 ± 0.34 log10 cfu/g) and total coliform counts (1.71±0.51 log Most Probable Number/g) significantly (p>0.05). However, the microbial counts were found to increase significantly (p<0.05) after the cooling process, except for the yeast and mold counts and Staphylococcus aureus counts. The presumptive predominant microorganisms, isolated before the boiling stage, were members of the Enterobacteriaceae family and those belonging to Pseudomonas, Vibrio, Staphylococcus, Bacillus and Micrococcus. After the boiling stage, the presumptive predominant microorganisms were members of Enterobacteriace family and those belonging to Micrococcus, Bacillus, Staphylococcus and Aerococcus.